2023
DOI: 10.3390/polym15010227
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight and High Impact Toughness PP/PET/POE Composite Foams Fabricated by In Situ Nanofibrillation and Microcellular Injection Molding

Abstract: Polypropylene (PP) has become the most promising and candidate material for fabricating lightweight products. Microcellular injection molding (MIM) is a cost-effective technology for manufacturing porous plastic products. However, it is still challenging to fabricate high-performance PP microcellular components. Herein, we reported an efficient strategy to produce lightweight and high impact toughness foamed PP/polyethylene terephthalate (PET)/polyolefin-based elastomer (POE) components by combining in situ fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The rheological property of polymer composite has a significant effect on foaming behavior [ 36 ]. Figure 3 illustrates the relationship between storage modulus (G′), complex viscosity (η*) and loss tangent (tan δ) with frequency (ω).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rheological property of polymer composite has a significant effect on foaming behavior [ 36 ]. Figure 3 illustrates the relationship between storage modulus (G′), complex viscosity (η*) and loss tangent (tan δ) with frequency (ω).…”
Section: Resultsmentioning
confidence: 99%
“…η* of INF composites is significantly higher than that of pure PP and melt-blended composites, particularly in the low frequency region. It can be explained that the PET fibril network can restrict the motion of PP molecular chains as a role of a skeleton within PP matrix [ 36 ]. It is noteworthy that the η* of PP/PET(S) composite decreased greatly after the introduction of PDPP particles, while the η* is almost kept constant for both INF composites.…”
Section: Resultsmentioning
confidence: 99%
“…This result is consistent with our previous works. 21,27 The immiscible nature of the PET phase and PP matrix, associated with strong elongation flow action during the INF process, are major factors influencing the formation of the fibrillar network. Additionally, the average diameter of PET fibrils in the PP/PET(F)/Talc composite is significantly reduced from 368 to 231 nm when compared with the PP/PET(F) sample.…”
Section: Inf Composite Morphologymentioning
confidence: 99%
“…In a PP composite, it is crucial to consider that the disperse phase has a small and evenly distributed particle size. Any changes in the morphology of the dispersed phase can affect the nucleation effect, which in turn affects the foam's quality 23,24 . Such as Wang et al 25 prepared PP/POE composites with “island” structure and co‐continuous structure.…”
Section: Introductionmentioning
confidence: 99%
“…Any changes in the morphology of the dispersed phase can affect the nucleation effect, which in turn affects the foam's quality. 23,24 Such as Wang et al 25 prepared PP/POE composites with "island" structure and co-continuous structure. Gong et al 26 found that the addition of POE could obviously enhance the foaming quality of PP.…”
Section: Introductionmentioning
confidence: 99%